Association of systemic inflammatory markers with clinical adverse prognosis and outcomes in HFpEF: a systematic review and meta-analysis of cohort studies - Fu, Zhenyue; Liu, Pengfei; Gao, Xiya; Shi, Shuqing; Li, Yumeng; Zhang, Bingxuan; Wu, Huaqin; Song, Qingqiao (Frontiers in Cardiovascular Medicine, 2024)
Objective: To evaluate the association between systemic inflammatory markers and clinical outcomes (all-cause mortality, cardiovascular mortality, and rehospitalization) in patients with heart failure with preserved ejection fraction (HFpEF).Methods: We conducted a comprehensive literature search in PubMed, Embase, and Ovid Medline databases from inception to June 27, 2024. Studies were included if they were observational clinical studies involving HFpEF patients over 18 years old, with exposure to systemic inflammatory markers and reporting on adverse prognosis outcomes. The Newcastle-Ottawa Scale (NOS) was used to assess study quality. Results: Eight studies ultimately included in the meta-analysis which involved 9744 participants from six countries. The meta-analysis showed that systemic inflammatory markers were significantly associated with all-cause mortality (HR 1.43, p<0.05), cardiovascular mortality (HR 2.04, 95% CI 1.33-3.12, p<0.05), and cardiovascular rehospitalization (HR 2.83, 95% CI 0.92-8.67, p<0.05) in HFpEF patients. Low heterogeneity was observed across studies (I² = 0.00%). Sensitivity and publication bias analyses indicated that the results were robust.Conclusion: Systemic inflammatory markers demonstrate significant predictive value for adverse clinical outcomes in HFpEF patients. The findings suggest that monitoring systemic inflammation may provide valuable prognostic information for clinicians managing HFpEF patients.